Super‐fast multipole method for power frequency electric field in substations. Issue 1 (2014) - ,; ,; ,; ,; ,
Abstract : Purpose – The purpose of this study is to calculate the frequency electric field in substation.Design/methodology/approach – The paper proposes a novel fast multipole method (FMM) called Super‐FMM to solve the PFEF problems in substations. The paper substitutes the original approaches for analytic expansions and translations through equivalent density representations.Findings – The paper shows that the Super‐FMM is more efficient in terms of the complexity of its storage spaces and computational costs compared with the best‐known FMM when placed under scenarios with exactly the same error rates.Research limitations/implications – Using the fast Fourier transform algorithm can further improve the optimization algorithm and computational efficiency.Originality/value – A novel FMM called Super‐FMM is proposed, which has a structure similar to that of the adaptive FMM algorithm, but the paper substitutes the original approaches for analytic expansions and translations through equivalent density representations. Acknowledgements : Zhanlong Zhang and Xuemei Xie et al. gratefully acknowledge the financial support for the Natural Science Foundations of Chongqing and the Independent Research Projects of State Key Laboratory of Power Transmission Equipment and System Security and New Technology.